A Cre-based double fluorescence indicator system for monitoring cell fusion events and selection of fused cells - Pfannkuche, Kurt (BioTechniques, 2010)
We have established an in vitro Cre/loxP-based assay for monitoring cell fusion events that specifically traces the transport of cytoplasm from one cell to its fusion partner. Cells with a double fluorescence vector indicate fusion with cells expressing Cre recombinase by switching expression from red to green fluorescent protein through a Cre-mediated recombination event that simultaneously activates puromycin-acetyltransferase expression. This strategy allows for both the observation and puromycin selection of indicator cells that have undergone fusion with a Cre recombinase-expressing partner. A fusion protein of Cre with estrogen receptor (ER) can be used to control Cre recombinase activity through the tamoxifen-induced translocation of the Cre-ER fusion protein to the nucleus. Here we have established a new methodology that not only allows the monitoring of the transport of cellular contents, but also enables the purification of fused cells using puromycin